Analisis Daya Saing SDM dalam Upaya Meningkatkan Prestasi Berusaha Pengusaha Industri Kecil di Kota Pekanbaru - rahman, fatkhur (Komunitas Manajemen Kompetitif, 2015)
Abstract: The purpose of this study was to determine the effect of competitiveness towards achievements to strive in a small industrial town of Pekanbaru. Whole object of this study is the small industrial entrepreneurs registered in the city of Pekanbaru the number of 1,545 people spread on five business groups namely food industry business, clothing, chemicals and building materials , metals and electronics and handicrafts. Therefore, the relative amount of the population defined as 94 samples using proportional random sampling method. The variables studied consisted of three independent variables and the dependent variable. The independent variable is competitiveness and while the dependent variable was trying achievement. The method used in this study is a quantitative method. The instrument used for data collection in the form questionnaire Likert scale models. Discussion and hypothesis testing are conducted through the processing path analysis techniques using SPSS 17. The results showed that the effect on the competitiveness of small entrepreneurship in the industry by entrepreneurial achievements of trying to influence the small industrial city of Pekanbaru with coefficient of 0,555. competitiveness of trying to influence the achievement of small industries in the city of Pekanbaru with the influence of competitiveness on the achievement represented by the coefficient beruasha meaningful reasons for wanting to be successful because it has the potential to succeed as a capital for entrepreneurs trying to businesses gain increasing and also the products more efficient. Keywords :Competitiveness, Achievement Sought